LOYALITAS PELANGGAN MELALUI PROGRAM SUBSIDI, COMPLAINT HANDLING DAN CITRA MEREK KORAN KOMPAS PADA PT. POLAMEDIA CIPTA NUSANTARA CABANG SOLO - Rinta Nurcahyati; Bambang Mursito; Eny Kustiyah (JURNAL ILMIAH EDUNOMIKA, 2020)
This study aims to determine customer loyalty through the subsidy program, complaint handling, and the image of Kompas Newspapers in PT Polamedia Cipta Nusantara. The dependent variable (Y) in this study is customer loyalty. Independent variable (X1) Subsidy program, (X2) Complaint handling, and (X3) Brand image. Methods of data analysis using multiple linear regression. This study used a sample of 100 respondents using simple random sampling techniques. Collecting data using a questionnaire that has passed the validity and reliability test Whereas for data programs using IBM SPSS 21.0 statistics. The analysis shows that there is a simultaneous and probability influence of the subsidy program variables, complaint handling and brand image on customer loyalty. Keyword: customer loyalty, subsidy programs, complaint handling, brand image